CURVA: RESISTENCIA VS TIEMPO, PARA HORMIGON DE ALTA RESISTENCIA f’c 55 mpa. COMPONENTES: ARENA DE RIO (km 26 vía a Penipe), ARIDO GRUESO (3/4¨ km 12 vía a San Luis), CEMENTO ESPECIAL TIPO 10P, ADITIVO SUPERPLASTIFICANTE ACELERANTE. - Guambo Lema, Luis Alfredo (2013)
The present work, describes and it analyzes the methodology applied for the curve: Resistance and Time, for concrete of high resistance f´c 55 MPa. The investigation leaves of the application of fundamental approaches of concretes of high resistance, besides a resistance to the high compression, characteristic of the concrete, for their dosage, setting in work and cured, it offers better benefits regarding permeability, resistance to the sulfates, to the reaction"arid-alkalis", resistance to the abrasion, etc.; that which confers them a bigger durability.